Identification of Gray Leaf Spot Disease Candidate Gene in Narrow-Leafed Lupin (Lupinus angustifolius L.) - Zhou, Gaofeng; Yang, Huaan; Renshaw, Daniel; Zou, Meilin; Thomas, Geoff; Li, Chengdao (Frontiers in Genetics, 2021)
Selection for resistance against grey leaf spot (GLS) is a major objective in the lupin breeding programs. A segregation ratio of 1:1 (resistant : susceptible) in F8 recombinant inbred lines (RIL8) derived from a cross between a breeding line 83A:476 (resistant to GLS) and a wild accession P27255 (susceptible to GLS) indicated that GLS was controlled by a single major gene. To develop molecular markers linked to GLS, in the beginning, only 11 resistant lines and six susceptible lines from the 83A:476 and P27255 population were genotyped with MFLP markers, and three MFLP markers were identified to be co-segregated with GLS. This method was very efficient. But the markers were located outside of the gene, and could not be used in other germplasms. Then QTL analysis and fine mapping were conducted to identify the gene. Finally, the gene was narrowed down to a 241 kb region containing two disease resistance genes. To further identify the candidate gene, DNA variants between accessions Tanjil (resistant to GLS) and Unicrop (susceptible to GLS) were analysed. The results indicated that only one SNP was detected in the 241 kb region. This SNP was located in the TMV resistance protein N-like gene region and also identified between 83A:476 and P27255. Genotyping the Tanjil/Unicrop RIL8 population showed that this SNP co-segregated with GLS resistance. The phylogenetic tree analysis of this gene among 18 lupin accessions indicates that Australian resistant breeding line/varieties were clustered into one group and carry two resistant alleles, while susceptible accessions were clustered into different groups.